TEXT “ALLA” AS AN OBJECT OF LINGVOFOLKLORE STUDY (Scientific journal of the Fergana State University, 2023)
The article examines the study of the text "Alla" in linguistic and folkloristic studies and reveals its unique linguistic picture of the children's world.